Developing an Air Travel Picture Dictionary in Enhancing Vocabulary Mastery Among Air Transport Management Students: A Need Analysis - Ginusti, Gallis Nawang; Ariebowo, Teguh (Universitas Hamzanwadi, 2023)
Proficiency in English, particularly in the specialized vocabulary of the aviation industry and air travel tourism, is crucial for effective communication and understanding. This study aims to explore the demand for an Air Travel Picture Dictionary among Air Transport Management students, addressing their specific linguistic challenges. Employing the first stage of the Research and Development (R&D) framework - Need Analysis, which is part of the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, this research utilizes a mixed-methods approach. Data was gathered from 141 Air Transport Management students, selected through random sampling, and complemented by semi-structured interviews with lecturers and industry practitioners. The findings reveal a significant reliance on English within the aviation sector, with specialized terminology being particularly prominent and crucial. Despite acknowledging its importance, students identified gaps in their vocabulary skills, notably in pronunciation, word meaning, word-class identification, and spelling. While online resources like Google Translate and search engines are commonly used for assistance, along with support from instructors and peers, traditional general English dictionaries and reference materials are less favored. Specialized aviation dictionaries specifically catering to air travel are seldom used. There is a pronounced interest among students for a bespoke Air Travel Picture Dictionary. Such a resource, they suggest, should encompass comprehensive vocabulary listings, pronunciation guides, clear word definitions, word class categorization, and visually engaging thematic illustrations that reflect the air travel process. This tool is envisioned to not only enhance their vocabulary but also to aid in better understanding the practical aspects of air travel in the aviation industry.